Selective Oxidation of Alcohols Catalyzed by Supported Nano‐Au Catalysts. Issue 47 (17th December 2019) - Zhang, Fang; Wang, Xiaoli; Wu, Gongde; Zhang, Changfei; Song, Shihao; Lan, Jianyang
Abstract: A series of Cu‐containing trimetal mixed oxides supported nano‐Au catalysts were prepared and characterized by XRD, N2 sorption, elemental analysis and H2 ‐TPR. Then, their catalytic performance was firstly investigated in the selective oxidation of glycerol with 3% H2 O2 or O2 as oxidants. It was found that both the elemental components of mixed oxides and the types of oxidant influenced remarkably the catalytic performance of the supported catalysts and the product distributions. Under the optimal reaction conditions, the highest yield of main product glyceric acid reached 66.5% over CuMnAl mixed oxide supported nano‐Au catalyst in the presence of O2 . Moreover, the catalyst could be reused several times. In addition, the catalyst was further used in the selective oxidation of benzyl alcohol and cyclohexanol, and the best yield of benzaldehyde and cyclohexanone were 72.5% and 96.0%, respectively. Abstract : Cu‐containing mixed oxides supported nano‐Au catalysts were promising catalysts for the selective oxidation of alcohols. The elemental composition of mixed oxide supports, the types of oxidants and the reaction conditions were found to influenced significantly the catalytic performance of catalysts and the product distributions. Moreover, the catalysts showed better stability and application prospect.